Let My People Go: Calgary Community Support for the Free Soviet Jewry Movement - Lipton, Saundra (Canadian Jewish Studies / Études juives canadiennes, 2025)
Activists in small Jewish population centres contributed significantly to the success of the Soviet Jewry movement. Yet, their activism is virtually disregarded in the literature. Through examination of the diversity of Soviet Jewry advocacy in Calgary, this paper demonstrates how one small Jewish centre contributed to the broader movement, thereby addressing the lacuna regarding the Soviet Jewry movement’s implementation in smaller cities across Canada. By positioning the Calgary activity within the larger national context, this study highlights the demographic and geographic challenges that both hindered and shaped the Calgary Soviet Jewry campaign while shedding light on its often-contentious relationship to the period’s primary Jewish governing body, the Canadian Jewish Congress.